2020
DOI: 10.1002/chem.202001003
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Oxide–Metal Strong Interaction (EOMSI)

Abstract: Strong metal–support interaction of supported metal catalysts is an important concept to describe the effect of metal–support interactions on the structures and catalytic performances of supported metal particles. By using an example of CeOx adlayers supported on Ag nanocrystals, herein a concept of electronic oxide–metal strong interaction (EOMSI) is put forward; this interaction significantly affects the electronic structures of oxide adlayers through metal‐to‐oxide charge transfer. The EOMSI can stabilize o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Later, surface science studies of well-defined oxide/metal model inverse catalysts have extensively demonstrated that, with the occurrence of OMI, oxide nanoparticles and thin films on metal single crystals exhibit electronic structures and chemical properties different from those found in bulk phases. Recently, oxide/metal inverse powder catalysts via depositions of oxide nanoparticles on supported or unsupported metal particles have emerged as a novel type of efficient catalysts, in which the observed OMI was found similar to those in the corresponding model inverse catalysts. For example, CeO x NPs on Au(111) and Cu(111) substrates and on Ag nanocrystals all exhibited rich oxygen vacancies. FeO bilayer film and islands on Pt(111) and Pt nanoparticles are stable under reductive atmospheres but get oxidized into FeO 2 under oxidative atmospheres. ,, The OMI usually occurs via electron transfer between metal substrates and supported oxide nanostructures, which is herein defined as EOMI. Very recently, a concept of EOMSI was put forward to specifically describe the strong EOMI capable of stabilizing supported oxide nanostructures in a low-oxidation state under an ambient condition, which individually is not stable, via charge transfer from metal substrates to supported oxide nanostructures. Moreover, the supported oxide nanostructures experiencing the EOMSI are resistant to high-temperature oxidation in air to certain an extent.…”
Section: Oxide–metal Interactions Of Oxide/metal Inverse Catalystsmentioning
confidence: 81%
See 3 more Smart Citations
“…Later, surface science studies of well-defined oxide/metal model inverse catalysts have extensively demonstrated that, with the occurrence of OMI, oxide nanoparticles and thin films on metal single crystals exhibit electronic structures and chemical properties different from those found in bulk phases. Recently, oxide/metal inverse powder catalysts via depositions of oxide nanoparticles on supported or unsupported metal particles have emerged as a novel type of efficient catalysts, in which the observed OMI was found similar to those in the corresponding model inverse catalysts. For example, CeO x NPs on Au(111) and Cu(111) substrates and on Ag nanocrystals all exhibited rich oxygen vacancies. FeO bilayer film and islands on Pt(111) and Pt nanoparticles are stable under reductive atmospheres but get oxidized into FeO 2 under oxidative atmospheres. ,, The OMI usually occurs via electron transfer between metal substrates and supported oxide nanostructures, which is herein defined as EOMI. Very recently, a concept of EOMSI was put forward to specifically describe the strong EOMI capable of stabilizing supported oxide nanostructures in a low-oxidation state under an ambient condition, which individually is not stable, via charge transfer from metal substrates to supported oxide nanostructures. Moreover, the supported oxide nanostructures experiencing the EOMSI are resistant to high-temperature oxidation in air to certain an extent.…”
Section: Oxide–metal Interactions Of Oxide/metal Inverse Catalystsmentioning
confidence: 81%
“…82,90,91 The OMI usually occurs via electron transfer between metal substrates and supported oxide nanostructures, which is herein defined as EOMI. Very recently, a concept of EOMSI 92 was put forward to specifically describe the strong EOMI capable of stabilizing supported oxide nanostructures in a low-oxidation state under an ambient condition, which individually is not stable, via charge transfer from metal substrates to supported oxide nanostructures. Moreover, the supported oxide nanostructures experiencing the EOMSI are resistant to high-temperature oxidation in air to certain an extent.…”
Section: Oxide−metal Interactions Of Oxide/metalmentioning
confidence: 99%
See 2 more Smart Citations
“…The shift of the N 1s peak to lower binding energy in BCET2 compared to the BT sample by 0.02 eV proves the engagement of BN nanosheets with Ce2O3 and TiO2 nanofibers [8]. According to the reported literatures [65], [66], [67], Ce2O3 will be stabilized through interaction by metal (Ag) and the charge transfer can stabilize Ce2O3. According to our results, there is charge transfer between Ce-Ti, and this interaction has stabilized Ce in +3 oxidation state.…”
Section: (1 H and I)mentioning
confidence: 70%